Peran Human Capital dalam Meningkatkan Daya Saing Perusahaan di Era Digital - Joshua Valerio; Aria Muhammad Dewantara; Rozaan Zhorif; Mohammad Zein Saleh (Jurnal Publikasi Ilmu Manajemen, 2025)
The rapid development of digital technology has significantly transformed business competition and requires companies to achieve sustainable competitive advantage. In this context, human capital has become a strategic factor that plays a crucial role in enhancing company competitiveness in the digital era. This study aims to analyze the role of human capital in improving corporate competitiveness through a literature review approach. Data were collected from various scientific sources, including academic journals, scholarly books, and reports from international organizations published between 2019 and 2025. The findings indicate that high-quality human capital, supported by strong digital competencies and continuous skill development, contributes significantly to improved organizational performance, innovation, and competitive advantage. Furthermore, effective human capital management through training, upskilling, and reskilling enhances a company’s adaptability to technological changes and dynamic market conditions. Therefore, this study concludes that human capital is a strategic asset and a key driver of sustainable competitiveness in the digital era.